Marcus Vinícius and the build-up path to the infused body: between the object of desire and the artwork (Palíndromo, 2015)
The artwork of the body artist Mar- cus Vinícius, analyzed in this paper, suggests a comprehension of the artist’s body as a fe- asible support to accumulation. Before the object of desire, the artist manages dialo- gues amongst imminent perceptions of the space inserted and the affections entwined with the object interior. Based on the stu- dies of the french philosopher Georges Ba- taille on the concept of Eroticism, Marcus Vinícius works question the designation In- fused Body (Corpo Injeto) considering it as an accomplishable support to the interla- cing with the work of art through the accu- mulation of formal and conceptual subject about this body that creates.
Keywords: Marcus Vinícius; infused body; accumulation; contemporary; body art